Integrating TPACK in literature education: contextualized lesson exemplars for Philippine and global texts - Aguda, Elaine; Delute, Regina Chriscel (Frontiers in Education, 2025)
This study aimed to develop Technological Pedagogical Content Knowledge (TPACK)-based lesson exemplars for 21st Century Literature of the Philippines and the World (21st CLPW) and investigate teachers’ perceived manifestation of their knowledge of content, pedagogy and technology and their extent of utilization of technology tools and strategies in the online teaching of literature. It used the Technological Pedagogical Content Knowledge Framework, which supports technology integration and lesson development across subject areas. It also surveyed a total population of 49 senior high school English teachers from private schools and a public university in Batangas City. Descriptive research method was utilized to analyze and interpret data. The findings revealed the respondents demonstrate their pedagogical knowledge to a very great extent while they manifest their technological knowledge and content knowledge to a great extent. Moreover, productivity tools were the most useful in the three stages of reading of online literature lesson while the most utilized strategies were lecture method, discovery method, cooperative learning, role-playing, and essays. Furthermore, there was a significant positive relationship between the extent of utilization of technology tools in the pre-reading and during-reading stage of online literature lesson and the extent of utilization of strategies under direct instruction, indirect instruction, interactive instruction, experiential instruction and independent study, while only interactive instruction had no significant relationship with the extent of utilization of technology tools in the post-reading. The study designed lesson exemplars for the online teaching of 21st CLPW and provided insights to teachers about technology integration and lesson development.